1986
DOI: 10.1161/01.res.58.6.839
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of cellular proliferation after arterial injury. IV. Heparin inhibits rat smooth muscle mitogenesis and migration.

Abstract: Heparin inhibits the development of intimal thickening after carotid injury in the rat; however, the specific cellular events responsible for this effect have not been defined. In this study, smooth muscle cell growth fraction and migration into the intima were quantitatively measured in heparin-treated animals. All rats were subjected to left carotid balloon injury and received continuous intraperitoneal infusion of tritiated thymidine; they were given either heparin or lactated Ringer's solution intravenousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
167
0
4

Year Published

1989
1989
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(182 citation statements)
references
References 21 publications
11
167
0
4
Order By: Relevance
“…38 In vitro, heparin inhibits smooth muscle cell migration and proliferation. 39 Our present data also indicate that heparin-like molecules can limit intimal proliferation in response to arterial wall immune injury. The content of intimal proliferation was also modified by heparin.…”
Section: Heparin Effectssupporting
confidence: 73%
“…38 In vitro, heparin inhibits smooth muscle cell migration and proliferation. 39 Our present data also indicate that heparin-like molecules can limit intimal proliferation in response to arterial wall immune injury. The content of intimal proliferation was also modified by heparin.…”
Section: Heparin Effectssupporting
confidence: 73%
“…RNA analysis revealed significantly decreased amounts ofPCNA mRNA in the antisense oligonucleotide-treated animals as compared with The initial wave of medial smooth muscle proliferation peaks at 72 h after balloon angioplasty in the rat carotid artery injury model (18). Given the effective suppression of PCNA message at 24 h, we then investigated the action of antisense 1 PCNA oligonucleotides, as compared with sense 1 control oligonucleotides, on the first wave of medial smooth muscle cell growth.…”
Section: Resultsmentioning
confidence: 99%
“…Heparin also is effective in reducing smooth muscle cell proliferation in vivo after arterial injury and is thus capable of counteracting the effects of local and blood borne growth factors. 169 Associated with this cessation of growth is an increase in the concentration of proteoglycans in injured arteries. 170 In vitro studies have also shown that arterial smooth muscle cell cultures accumulate more proteoglycan in the presence of heparin.…”
mentioning
confidence: 99%